TRACKING IMPACT OF LEADERSHIP TO CREATIVITY IN PT. TELUK LAMONG : WHERE ARE THE MODERATION VARIABLES COME FROM? - Herlambang, Pandhu; Yulianti, Praptini; Erlando, Angga (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
The COVID-19 pandemic situation is a challenge for most aspects of an organization or company. The same is the case with companies that oversee port affairs, which are an important means in the activities of sea transportation services. PT. Terminal Teluk Lamong is a subsidiary of 3rd Regional PT. Pelabuhan Indonesia. Utilization of information and communication technology, is an effort to accelerate the company in responding to community needs. In addition, aspects of human resources are not spared from this study. Leadership is one of the benchmarks for the success of a company. Even so, the relationship between leaders and employees is a form of true success. Empowering leaders are able to encourage employees to think actively and creatively in solving company problems. This research aims to determine the influence of empowering leadership behavior, creative self-efficacy, motivation to learn, trust in leaders, and employee creativity of PT. Terminal Teluk Lamong. This study uses quantitative methods through a questionnaire survey on 100 organic employees of PT. Teluk Lamong Terminal which is 26-40 years old. The data obtained were tested through the SmartPLS 3 statistical test tool. The variable of empowering leadership behavior is the independent variable, the variable of motivation to learn and creative self-efficacy is the intervention variable, and the variable of trust in the leader is the moderating variable. The findings of this study indicate that empowering leaders have a positive and significant impact on employee creativity. Furthermore, learning motivation and self-creative efficacy also partially mediate the influence of empowering leader behavior on employee creativity. Finally, the variable trust in the leader is able to accelerate the creative process of employees at work. Keywords:Leadership, Self-Efficacy, Employee Creativity, Trust.